A SRF touch screen and its laminating process
By using the SRF membrane and copper mesh layer in the traditional polarizer, combined with the LED backlit module and special optical glue to build the SRF touch screen, solve the problem of rainbow pattern in the traditional polarized film, and improve the display effect and response speed.
Patent Information
- Application Number
- CN202410843206.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The common rainbow pattern problems in traditional polarized films lead to poor display results and insufficient response speed and sensitivity.
The SRF membrane instead of the traditional TAC film, and by plating the copper grid layer on the SRF membrane, combining the LED backlit module and special optical glue to build a layered structure of the SRF touch screen.
A significant reduction of the emergence of the rainbow pattern, improved the display effect and viewing experience, and at the same time improve the response speed and sensitivity of the touch screen.
Smart Images

Figure CN118605752B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of touch screens, and in particular to an SRF touch screen and a laminating process thereof. Background Art
[0002] Touch screens are commonly used as an interface mechanism for electronic devices such as tablets, smartphones, and computers. A touch screen combines a display that provides output with a touch panel that captures input. The touch panel can be implemented, for example, as a resistive touch panel or a capacitive touch panel.
[0003] CN117251080A discloses an anti-moiré oversized metal grid touch screen, which is composed of multiple layers of components, including a cover plate, an upper optically transparent adhesive (OCA) adhesive, a receiving (RX) conductive film, a middle OCA adhesive, a transmission (TX) conductive film, a lower OCA adhesive, an interference layer, and a display module from the outside to the inside. The key innovation is that an interference layer with an irregular geometric pattern is introduced at the bottom of the metal grid, and the metal lines of the RX and TX conductive films can be freely set at an angle without being restricted by the RGB array of the display module. This design creates an irregular light output surface by combining an irregular interference layer with a regular metal grid, effectively reducing mesh interference.
[0004] CN116860121A discloses an ultra-large-size, screen-effective, UV-resistant metal grid touch screen, comprising electrodes, OCA glue and a cover plate, wherein the electrodes comprise a lower electrode and an upper electrode, and the OCA glue comprises common OCA and UV-resistant OCA, wherein the common OCA is between the lower electrode and the upper electrode, and the UV-resistant OCA is between the upper electrode and the cover plate, and the UV-resistant OCA comprises 10% to 15% of an anti-UV additive. By changing the formula of the OCA glue, in the conventional OCA glue, an appropriate amount of anti-UV particles or UV absorbers and other additives are added, the proportion of which is between 10% and 15%, and the UV-band light can be blocked by 98%, which can effectively prevent the product from yellowing and appropriately extend the final service life of the product. Summary of the invention
[0005] SRF polarizing film is an advanced optical material, and its structure consists of three layers: SRF film, PVA film and another layer of SRF film. This structure is different from the traditional polarizing film, which is usually composed of TCA film, PVA film and another layer of TCA film. Here, TCA stands for triacetyl cellulose, which is a commonly used protective film material. And SRF stands for super-refractive polyester film, which is a special film with excellent optical properties.
[0006] The term "super-refractive" in the field of optical materials refers to a specially designed optical effect that involves multiple refractions and reflections that light waves experience when passing through a film. This complex optical behavior causes the propagation direction of the light wave to change, thereby achieving a specific optical effect. In polyester film, this effect is achieved by precisely controlling the film's thickness, refractive index, and multilayer structure design.
[0007] The advantage of SRF polarizing film lies in its excellent optical performance. By improving the delay, SRF polarizing film can effectively solve the rainbow pattern problem common in traditional polarizing film. Rainbow pattern is caused by multiple reflections and refractions of light in the multi-layer film structure, resulting in the appearance of color stripes at a specific viewing angle. This problem is more common in traditional TAC film / PVA film / TAC film structure. After using SRF film to replace TAC film, the appearance of rainbow pattern can be significantly reduced, thereby improving the display effect and viewing experience.
[0008] To achieve the above object, the present invention provides a SRF touch screen, which is composed of the following layered structures in sequence: a cover plate, a metal grid layer, an SRF polarizing film, a metal grid layer, an SRF polarizing film, and an LED backlight module.
[0009] Preferably, the cover plate is a glass cover plate.
[0010] Preferably, the first metal grid layer is a copper grid plated on the first SRF polarizing film, with a grid line width of 2-8 μm; the second metal grid layer is a copper grid plated on the first SRF polarizing film, with a grid line width of 2-8 μm.
[0011] Preferably, the electrical polarization direction of the first SRF polarizing film is consistent with that of the second SRF polarizing film.
[0012] Preferably, the cover plate, the first metal mesh layer / the first SRF polarizing film, the second metal mesh layer / the second SRF polarizing film, and the LED backlight module are bonded together using optical adhesive.
[0013] Preferably, the optical adhesive comprises the following raw materials in parts by weight: 90-95 parts of acrylic monomer, 0.1-3 parts of photoinitiator, 0.1-2 parts of antioxidant and 5-10 parts of titanate coupling agent; the preparation method of the optical adhesive is: 90-95 parts of acrylic monomer, 0.1-3 parts of photoinitiator, 0.1-2 parts of antioxidant and 5-10 parts of titanate coupling agent are mixed uniformly under nitrogen, magnetically stirred for 30-60 minutes at 10-30°C and nitrogen atmosphere; vacuum degassing for 10-30 minutes; irradiating for 10-30 seconds under a 3W ultraviolet lamp with a wavelength of 405nm to obtain a mixture of prepolymer and monomer, i.e., an optical adhesive for SRF touch screen.
[0014] Preferably, the acrylic monomer is at least one of isooctyl acrylate, hydroxyethyl acrylate, and monomethacrylate phthalate.
[0015] Preferably, the photoinitiator is any one of photoinitiator 184, 1-hydroxycyclohexyl phenyl ketone, photoinitiator 2959, 2-hydroxy-2-methyl-1-phenylpropanone, and 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone.
[0016] The antioxidant is at least one of antioxidant 168, antioxidant 1010 and antioxidant 1076.
[0017] The titanate coupling agent is at least one of isopropyl triisostearate titanate and isopropyl tri(dioctyl pyrophosphate) titanate.
[0018] The present invention also discloses a bonding process of the SRF touch screen: copper is fixed on the surface of the SRF polarizing film by electroplating to obtain a first metal mesh layer / a first SRF polarizing film and a second metal mesh layer / a second SRF polarizing film respectively; an LED backlight module, a second metal mesh layer / a second SRF polarizing film, a first metal mesh layer / a first SRF polarizing film and a cover plate are sequentially bonded by optical adhesive to obtain the SRF touch screen.
[0019] Beneficial effects of the present invention:
[0020] The traditional polarizing film is a TAC film / PVA film / TAC film structure. Due to multiple reflections and refractions of light in the multi-layer film structure, color stripes appear at a specific viewing angle, commonly known as rainbow stripes. The present invention uses SRF film to replace TAC film, which can significantly reduce the appearance of rainbow stripes by improving the delay, thereby improving the display effect and viewing experience. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a structural diagram of the SRF touch screen. DETAILED DESCRIPTION
[0022] Example 1
[0023] An SRF touch screen is composed of the following layered structures in sequence: a glass cover plate, a first metal grid layer, a first SRF polarizing film, a second metal grid layer, a second SRF polarizing film, and an LED backlight module.
[0024] The specific bonding process is as follows:
[0025] Copper is fixed on the surface of the SRF polarizing film by electroplating to obtain a first metal mesh layer / a first SRF polarizing film and a second metal mesh layer / a second SRF polarizing film respectively; an LED backlight module, a second metal mesh layer / a second SRF polarizing film, a first metal mesh layer / a first SRF polarizing film and a cover plate are sequentially bonded by optical adhesive to obtain the SRF touch screen.
[0026] The first metal grid layer is a copper grid plated on a first SRF polarizing film, with a grid line width of 6 μm; the second metal grid layer is a copper grid plated on a second SRF polarizing film, with a grid line width of 6 μm. The first SRF polarizing film and the second SRF polarizing film have the same electrical polarization direction.
[0027] The bonding process is dispensing → lamination → leveling → curing; the thickness of the optical glue is controlled at 150μm.
[0028] The optical adhesive may be any one of Examples 2-4 and Comparative Example 1.
[0029] Example 2
[0030] The preparation method of the optical adhesive is as follows: 900g of monomer, 5g of photoinitiator, 5g of antioxidant and 60g of titanate coupling agent are mixed evenly under nitrogen, and magnetically stirred for 60min at 15°C and nitrogen atmosphere; vacuum degassing for 30min; irradiating under a 3W, 405nm wavelength ultraviolet lamp for 20s to obtain a mixture of prepolymer and monomer, i.e., optical adhesive.
[0031] The monomer is obtained by mixing isooctyl acrylate and hydroxyethyl acrylate in a mass ratio of 2:1.
[0032] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0033] The antioxidant is antioxidant 168.
[0034] The titanate coupling agent is isopropyl titanate triisostearate (CAS No.: 61417-49-0).
[0035] Comparative Example 1
[0036] The preparation method of the optical adhesive is as follows: 900g of monomer, 5g of photoinitiator and 5g of antioxidant are mixed evenly under nitrogen, and magnetically stirred for 60min at 15°C and nitrogen atmosphere; vacuum degassing for 30min; irradiating under a 3W, 405nm wavelength ultraviolet lamp for 20s to obtain a mixture of prepolymer and monomer, i.e., optical adhesive.
[0037] The monomer is obtained by mixing isooctyl acrylate and hydroxyethyl acrylate in a mass ratio of 2:1.
[0038] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0039] The antioxidant is antioxidant 168.
[0040] Example 3
[0041] The preparation method of the optical adhesive is as follows: 900g of monomer, 5g of photoinitiator, 5g of antioxidant and 60g of titanate coupling agent are mixed evenly under nitrogen, and magnetically stirred for 60min at 15°C and nitrogen atmosphere; vacuum degassing for 30min; irradiating under a 3W, 405nm wavelength ultraviolet lamp for 20s to obtain a mixture of prepolymer and monomer, i.e., optical adhesive.
[0042] The monomer is obtained by mixing isooctyl acrylate and monomethacrylate phthalate in a mass ratio of 2:1.
[0043] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0044] The antioxidant is antioxidant 168.
[0045] The titanate coupling agent is isopropyl titanate triisostearate (CAS No.: 61417-49-0).
[0046] Example 4
[0047] The preparation method of the optical adhesive is as follows: 900g of monomer, 5g of photoinitiator, 5g of antioxidant and 60g of titanate coupling agent are mixed evenly under nitrogen, and magnetically stirred for 60min at 15°C and nitrogen atmosphere; vacuum degassing for 30min; irradiating under a 3W, 405nm wavelength ultraviolet lamp for 20s to obtain a mixture of prepolymer and monomer, i.e., optical adhesive.
[0048] The monomer is obtained by mixing hydroxyethyl acrylate and phthalic acid monomethacrylate in a mass ratio of 1:1.
[0049] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0050] The antioxidant is antioxidant 168.
[0051] The titanate coupling agent is isopropyl titanate triisostearate (CAS No.: 61417-49-0).
[0052] The parameters and sources of some raw materials in the embodiments of the present invention are as follows:
[0053] Isooctyl acrylate, referred to as EHA, CAS number: 29590-42-9.
[0054] Hydroxyethyl acrylate, referred to as HEA, CAS number: 818-61-1.
[0055] Phthalic acid monomethacrylate, CAS number: 27697-00-3.
[0056] 1-Hydroxycyclohexylphenyl ketone, CAS number: 947-19-3.
[0057] Isopropyl titanate triisostearate, CAS number: 61417-49-0.
[0058] Isopropyl tri(dioctyl pyrophosphate) titanate, CAS number: 67691-13-8.
[0059] Test Example 1
[0060] The optical adhesive in Examples 2-4 and the comparative example was coated on a release film and then covered with another release film, sandwiched between two pieces of glass, separated by a 0.2mm thick flat silicone pad and rolled 10 times with a roller to remove bubbles; irradiated under a 3W, 405nm wavelength ultraviolet lamp for 300s, and the optical properties of the obtained optical adhesive were tested. The thickness of the optical adhesive was controlled to be 150μm by the coating amount. The transmittance meter DR81 was used for testing, and the specific results are as follows:
[0061] Table 1
[0062] Light transmittance Example 2 94.55% Comparative Example 1 94.52% Example 3 95.43% Example 4 99.31%
[0063] By comparing the examples and the control examples, it can be found that the addition of isopropyl titanate triisostearate has little effect on the acrylic optical adhesive. The light transmittance of the optical adhesive prepared by using hydroxyethyl acrylate and monomethacrylate phthalate as mixed monomers and isopropyl titanate triisostearate is significantly better than that of the optical adhesive prepared by using isooctyl acrylate and monomethacrylate phthalate as mixed monomers and isooctyl acrylate and hydroxyethyl acrylate as mixed monomers. The possible reason is that hydroxyethyl acrylate and monomethacrylate phthalate as mixed monomers can promote lower crystallinity, reduce light scattering, and thus improve light transmittance.
[0064] Test Example 2
[0065] The optical adhesives of the embodiments and the control examples were tested using the dielectric constant test method described in GB / T1693-2007 “Determination of dielectric constant and dielectric loss tangent of vulcanized rubber”.
[0066] The optical adhesives in Examples 2-4 and Comparative Examples were coated on a release film and then covered with another release film, sandwiched between two pieces of glass, separated by a 0.2mm thick flat silicone pad and rolled 10 times with a roller to remove bubbles; irradiated under a 3W, 405nm wavelength UV lamp for 300s, and the obtained optical adhesives were subjected to dielectric constant testing. The thickness of the optical adhesive was controlled to be 150μm by the coating amount.
[0067] Table 2
[0068] <![CDATA[Dielectric constant (C 2 / (N·m 2 ))]]> Example 2 2.23 Comparative Example 1 2.63 Example 3 2.31 Example 4 1.84
[0069] Optically clear adhesives (OCA) are widely used in various touch screen devices, including smartphones, tablets, laptops, car display systems, and industrial touch screens. These devices have strict requirements on the response speed and sensitivity of the touch screen. The sensitivity of the touch screen is closely related to the delay of signal transmission. Shortening the delay time can significantly improve the response speed of the touch screen.
[0070] The dielectric constant of optical adhesive is a key factor affecting signal transmission delay. OCA with lower dielectric constant helps reduce signal lag during transmission, mainly because low dielectric constant materials allow electric fields to propagate faster in the material, thereby reducing the signal propagation time. Therefore, by selecting OCA materials with lower dielectric constants, the signal transmission delay can be effectively reduced, thereby improving the sensitivity and overall performance of the touch screen.
[0071] When designing high-performance touch screens, considering the dielectric constant of OCA is an important step to achieve fast response and high-sensitivity operation. By optimizing the dielectric properties of OCA, the user experience can be improved to meet the needs of modern touch screen devices for fast and accurate operation.
[0072] By comparing Comparative Example 1 with Example 2, it can be found that the addition of isopropyl titanate triisostearate during the synthesis of acrylic optical adhesive can effectively reduce the dielectric constant of acrylic optical adhesive. The possible reason is that isopropyl titanate triisostearate can promote the disordered arrangement of polymer chains, increase the free volume of polymers, reduce the interaction between molecules, and thus reduce the dielectric constant. Isopropyl titanate triisostearate can increase the crosslinking density of the polymer network and restrict the movement of polymer chains, thereby reducing polarization under the action of an electric field and reducing the dielectric constant.
[0073] By comparing Examples 2-4, it can be found that the optical adhesive prepared by using hydroxyethyl acrylate and monomethacrylate phthalate as mixed monomers and isopropyl titanate triisostearate has a lower dielectric constant than that prepared by using isooctyl acrylate and monomethacrylate phthalate as mixed monomers and isooctyl acrylate and hydroxyethyl acrylate as mixed monomers. The possible reason is that hydroxyethyl acrylate and monomethacrylate phthalate as mixed monomers can form a more disordered molecular chain arrangement, reduce the interaction between molecules, increase the free volume, weaken the polarization of the molecular chain in the electric field, and achieve a low dielectric constant.
Claims
1. A SRF touch screen, characterized in that: The SRF touch screen is composed of the following layered structures in sequence: a cover plate, a first metal mesh layer, a first SRF polarizing film, a second metal mesh layer, a second SRF polarizing film, and an LED backlight module; The first metal grid layer is a copper grid plated on a first SRF polarizing film, and the grid line width is 2-8 μm; the second metal grid layer is a copper grid plated on a second SRF polarizing film, and the grid line width is 2-8 μm; The electrical polarization directions of the first SRF polarizing film and the second SRF polarizing film are consistent; The cover plate, the first metal mesh layer / the first SRF polarizing film, the second metal mesh layer / the second SRF polarizing film, and the LED backlight module are bonded together using optical adhesive; The optical adhesive comprises the following raw materials in parts by weight: 90-95 parts of acrylic monomer, 0.1-3 parts of photoinitiator, 0.1-2 parts of antioxidant and 5-10 parts of titanate coupling agent; the preparation method of the optical adhesive is: 90-95 parts of acrylic monomer, 0.1-3 parts of photoinitiator, 0.1-2 parts of antioxidant and 5-10 parts of titanate coupling agent are mixed uniformly under nitrogen atmosphere, magnetically stirred for 30-60 minutes at 10-30° C. and nitrogen atmosphere; vacuum degassing for 10-30 minutes; irradiating for 10-30 seconds under 3W ultraviolet lamp with a wavelength of 405nm to obtain a mixture of prepolymer and monomer, namely the optical adhesive; The acrylic acid monomer is obtained by mixing hydroxyethyl acrylate and phthalic acid monomethacrylate in a mass ratio of 1:1; The titanate coupling agent is isopropyl titanate triisostearate.
2. The SRF touch screen according to claim 1, characterized in that: The cover plate is a glass cover plate.
3. The SRF touch screen according to claim 1, characterized in that: The photoinitiator is any one of photoinitiator 184, 1-hydroxycyclohexyl phenyl ketone, photoinitiator 2959, 2-hydroxy-2-methyl-1-phenylpropanone, and 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone; the antioxidant is at least one of antioxidant 168, antioxidant 1010, and antioxidant 1076.
4. The laminating process of the SRF touch screen according to any one of claims 1 to 3, characterized in that: Copper is fixed on the surface of the SRF polarizing film by electroplating to obtain a first metal mesh layer / a first SRF polarizing film and a second metal mesh layer / a second SRF polarizing film respectively; an LED backlight module, a second metal mesh layer / a second SRF polarizing film, a first metal mesh layer / a first SRF polarizing film and a cover plate are sequentially bonded by optical adhesive to obtain the SRF touch screen.
Citation Information
Patent Citations
UV curing-type thermal-melt optical clear adhesive (TOCA) and bonding method
CN103820043A
Acrylate OCA optical adhesive film, and preparation method and application thereof
CN106590484A
Touch module
CN107861659A
Flexible touch display screen
CN208207770U